“THE KINGFISHER MIGHT CATCH FIRE AGAIN, REDUCING EVERYTHING TO ASHES”: ON THE INTERTEXTUAL RESONANCES OF GRECO-BRITISH POETICS IN MICHAEL DAVID O’BRIEN’S “THE FATHER’S TALE”he Father’s Tale” - de Oliveira Casemiro Pereira de Amorim, Victor Hugo (Revista de Letras Norte@mentos, 2025)
This paper seeks to explore the intertextual elements within Michael David O’Brien’s The Father’s Tale by focusing on its connections to Greek mythology, particularly the myth of Alcyone, and Gerard Manley Hopkins’ poem As Kingfishers Catch Fire. Through literary allusions and symbolic imagery, O’Brien’s novel thoroughly engages with existential themes, where intertextuality becomes a crucial element in the protagonist’s journey. By weaving together past literary traditions and contemporary storytelling, the textual-author – the narrator – enriches the narrative by offering readers a multilayered experience that blends literature, memory, and meaning, thus creating an exploration of the human condition.